The Multi-Functional Roles of CCR7 in Human Immunology and as a Promising Therapeutic Target for Cancer Therapeutics - Alrumaihi, Faris (Frontiers in Molecular Biosciences, 2022)
An important hallmark of the human immune system is to provide adaptive immunity against pathogens but tolerance toward self-antigens. The CC-chemokine receptor 7 (CCR7) provides a significant contribution in guiding cells to and within lymphoid organs and is important for acquiring immunity and tolerance. The CCR7 holds great importance in establishing thymic architecture and function and naïve and regulatory T-cell homing in the lymph nodes. Similarly, the receptor is a key regulator in cancer cell migration and the movement of dendritic cells. This makes the CCR7 an important receptor as a drug and prognostic marker. In this review, we discussed several biological roles of the CCR7 and its importance as a drug and prognostic marker.